EVALUASI KEBUTUHAN DAN PENGGUNAAN RUANG TERBUKA HIJAU TAMAN DI KELURAHAN CENGKARENG TIMUR (Universitas Esa Unggul, 2018)
Green Open Space (RTH) is a space that functions as a place for human life, both individually and in groups, as well as a place for other creatures to live and breed sustainably. Provision of Green Open Space (RTH) is a mandate of Law No. 26/2007 concerning Spatial Planning where Green Open Space is required 30% of the total urban area divided into public green openings of at least 20% and private green open space of at least 10%. Cengkareng Timur Village has an area of 451.50 Ha with a population of 87,180 and a population density of 19 people / m2, Cengkareng Timur Village has an area of 7.66 Ha of Green Open Space / Park which is divided into several RWs in East Cengkareng Village. The Green Open Space / park available in Cengkareng Timur Village is intended for playgrounds as well as environmental parks. However, some of the available parks look neglected and there are rarely residents who use them. To obtain a comprehensive picture of the Needs and Uses of Green Open Space observations and analyzes of needs and uses are carried out. Based on the results of observations drawn conclusions; the available physical condition of the green open space of the park is maintained and not maintained; the distribution of RTH in the park is uneven and the use of RTH in the park most often occurs in the morning with activities that are often carried out in RTH Taman is socializing. In order for users to be more comfortable, it is necessary to add garden support facilities, such as benches, garden lights and children's play facilities.Â Keywords: Green Open Space, use, needs, Cengkareng Timur Village